Evaluation criteria for velocity distributions in front of bulb hydro turbines. (June 2018) - Gabl, Roman; Innerhofer, Daniel; Achleitner, Stefan; Righetti, Maurizio; Aufleger, Markus
Abstract: General guidelines are available for the design of intake structures in river power plants. Nearly all existing criteria are limited in scope to a (rectangular) control section near the trash rack. In this section, a homogeneous flow with negligible wall influence is defined as the ideal condition. 3D numerics can simulate the complete velocity field up to the turbine, and therefore inform investigations of different inflow structure variations. This paper presents a review of six existing criteria and a modification of the Fisher-Franke criterion. All criteria are tested for both theoretical pipe flow conditions and artificial biased velocity distributions, for which different simplified obstacles in front of a turbine are investigated with the help of the 3D numerical software ANSYS-CFX. The best results could be achieved using the evaluation of the kinetic energy flux coefficient as well as the new modified criterion. Both can be recommended for the geometry optimisation of the intake structure. Highlights: Existing criteria define a constant velocity distribution (VD) as perfect. Those are not applicable under pipe flow conditions in front of a turbine (Kaplan). A newly developed criterion allows to include the near wall effects. Tested with data sets based on theoretical VD and also artificially biased VD.